2005
DOI: 10.1002/eji.200525849
|View full text |Cite
|
Sign up to set email alerts
|

A novel apoptosis-inducing anti-PSGL-1 antibody for T cell-mediated diseases

Abstract: We previously discovered a hamster monoclonal antibody, TAB4, against mouse PSGL-1/CD162 that can induce death of activated T cells. Here, we further investigated the potential of TAB4 in treating two murine models of T cell-mediated diseases. The results showed that administration of TAB4 suppressed incidence and severity of both GVHD and type I diabetes. Analyses of apoptotic T cells ex vivo shortly after antibody injection revealed a higher percentage of apoptosis among activated T cells in the TAB4-treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…We consider that our findings will contribute to further understand the physiological role of PSGL-1 in the immune system, and the complexity of the different stimuli for the induction of immune tolerance. In addition, our findings may have practical relevance because it has been proposed that PSGL-1 is a potential target for the therapy of autoimmune and inflammatory diseases (41,52,53).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…We consider that our findings will contribute to further understand the physiological role of PSGL-1 in the immune system, and the complexity of the different stimuli for the induction of immune tolerance. In addition, our findings may have practical relevance because it has been proposed that PSGL-1 is a potential target for the therapy of autoimmune and inflammatory diseases (41,52,53).…”
Section: Discussionmentioning
confidence: 71%
“…Because PSGL-1 has been widely considered as an adhesion receptor that generates activating signals in leukocytes, our findings are unexpected. However, there are previous reports on a regulatory role of PSGL-1 on bone marrow-derived cells, mainly on the proliferation of CD34 ϩ hemopoietic progenitor cells and on the cell survival of activated T lymphocytes (34,40,41). The possible role of PSGL-1 on DCs in central lymphoid tissues is of interest and it is very feasible that during their differentiation in the bone marrow, immature DCs are exposed to the engagement of their PSGL-1 molecules by their ligands, mainly Eand P-selectins.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that PSGL-1 mediates cell apoptosis by accumulation and activation of leukocytes that induce apoptotic factors. Interestingly, a recent report indicated that in activated lymphocytes, PSGL-1 mediated signaling may actually accelerate apoptosis and suppress GVHD (46). Inhibition of leukocytes and endothelial cells interaction may have important antiapoptotic and protective effects in hepatic IRI.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of CD162 on polymorphonuclear leukocytes, monocytes and T lymphocytes could represent a possible issue of concern for the therapeutic employment of anti-CD162 monoclonal antibodies. However, no significant adverse events or toxicities have been observed in anti-PSGL1-treated mice [76], and PSGL-1 knockout mice have not shown increased susceptibility to infections [80]. Furthermore, the reported ability of anti-PSGL1 treatment to induce apoptosis of activated T-cells may represent a useful addition to its antimyeloma effect by controlling GVHD in patients receiving allogeneic stem cell transplantation.…”
Section: Cd74mentioning
confidence: 96%
“…PSGL-1 is also expressed in dendritic cells, platelets and endothelial cells of different sites [73]. Following the interaction with its ligands, CD162 activates different intracellular signaling pathways involving various protein kinases [74], and participates in the immune response regulatory mechanisms by either inducing or preventing apoptosis in T lymphocytes [75,76], depending on their stage of activation, and by inducing the development of tolerogenic dendritic cells [77]. CD162 has been found to be constitutively expressed in indolent and aggressive plasma cell disorders, including MM, and in normal plasma cells [78].…”
Section: Cd74mentioning
confidence: 99%